An Infrared and Raman Spectroscopic Study of Metal II Di 2 Methylpyridine Tetracyanonickelate Complexes - AKYÜZ, SEVİM (Kluwer Academic Publishers, 1985)
The results of an infrared and Raman spectroscopic study are reported for two new metal 2-methylpyridine tetracyanonickelate complexes, M(C6H7N)2Ni(CN)4, M=Ni or Cd. Their structure consists of corrugated polymeric layers of {M-Ni(CN)4}∞ with 2-methylpyridine molecules bound directly to the metal (M). These complexes can act as host lattices in the formation of inclusion compounds with dioxane guest molecules.
Keywords: 2-methylpyridine; tetracyanonickelate complex; inclusion compound; infrared and Raman spectra